Kontemplacyjny wymiar życia zakonnego - Bartoszewski, Gabriel (Prawo Kanoniczne, 1981)
In contem porary religious life there ex ists a very sharp tension b etw een exterior activity and spiritual life. M any resign from prayer under the pretext, that th ey w ill be able to m ore fu lly involve them selves in their w ork, as it w ere giving m ore of them selve!s to exterior activity. M any religious have a m istaken understanding of contem plation as a u seless and irresponsible concentration on on e’s self. The Second V atican Council how ever m ade a clear and decisive statem en t in this m atter; all religious are called both to contem plation and apostolic love. It w as for this reason that the Concil did aw ay w ith th e previous division b etw een the contem plative and apostolic institutes. U nion w ith C hrist m ust be th e esential substance o f both the in d ividual religious and th e com m unities of religious institutes; it is one o f the m ost irreplaceable elem ents of religious life. Im portant factors such as listen in g to and m editating upon the Word of God, Eucharist as w ell as com m unal and individual prayer play a basic role in m aintaining th e con tem plative character of religious life. A m ong th ese factors w hich support th e contem plative dim ension of religiou s life axe found: com m on life and a m utual sharing of the experiences of faith. A m ong the m ain dangers threatening religious life w e should in clu d e th e follow ing: excess of w ork and th e stresses resulting th erefrom , an attitu d e of consum ption on the part of som e religious and a prevailing confusion w ith respect to basic th eological concetpts. A ll religious should b e concerned w ith the preservation of th e contem p lative dim ension of religious life. Superiors on all lev els how ever p lay th e m ain role. In their pastoral and adm inistrative w ork, su - in m ind. R eligious life is a sign, a sign of another life. Today, as in the days of the A postles, peop le h a v e recourse to us w ith th e plea on thir lips „We want to see Jesus” (John 12, 21).